Management of Gallstones and Acute Cholecystitis in Patients with Liver Cirrhosis: What Should We Consider When Performing Surgery? - Shang Yu Wang; Chun Nan Yeh; Yi Yin Jan; Miin Fu Chen (Gut and Liver, 2021)
Acute cholecystitis and several gallbladder stone-related conditions, such as impacted common bile duct stones, cholangitis, and biliary pancreatitis, are common medical conditions in daily practice. An early cholecystectomy or drainage procedure with delayed cholecystectomy is the current standard of treatment based on published clinical guidelines. Cirrhosis is not only a condition of chronically impaired hepatic function but also has systemic effects in patients. In cirrhotic individuals, several predisposing factors, including changes in the bile acid composition, increased nucleation of bile, and decreased motility of the gallbladder, contribute to the formation of biliary stones and the possibility of symptomatic cholelithiasis, which is an indication for surgical treatment. In addition to these predisposing factors for cholelithiasis, systemic effects and local anatomic consequences related to cirrhosis lead to anesthesiologic risks and perioperative complications in cirrhotic patients. Therefore, the treatment of the aforementioned biliary conditions in cirrhotic patients has become a challenging issue. In this review, we focus on cholecystectomy for cirrhotic patients and summarize the surgical indications, risk stratification, surgical procedures, and surgical outcomes specific to cirrhotic patients with symptomatic cholelithiasis.